Pengaruh Penggunaan Media Kartu Kata Bergambar terhadap Kemampuan Membaca Permulaan pada Peserta Didik Kelas B TK Nurfalah Tattakang kabupaten Gowa - Qolby, Nurul; Ismail, Wahyuni; Maulana, Andi; Munirah; T, M. Yusuf (Al Asma: Journal of Islamic Education, 2023)
This research aims to determine the effect of using picture word card media on the beginning reading abilities of class B students at Nurfalah Tattakang Kindergarten, Gowa Regency. This research is pre-experimental with a research design, namely one group pretest-posttest design. The population in this study were early childhood children aged 5-6 years, with a total of 15 people in Nurfalah Tattakang Kindergarten. The research sample involved Class B of Nurfalah Tattakang Kindergarten, Gowa Regency, which was selected through saturated sampling. This research uses instruments in the form of observation and documentation sheets. The data obtained was then analyzed using descriptive statistics. This research showed increased initial reading ability through picture word cards in class B students at Nurfalah Tattakang Kindergarten, Gowa Regency. Thus, picture word cartoon media can be used to improve students' initial reading skills.